2019
DOI: 10.1111/nph.15991
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the onset of autumn leaf senescence in deciduous forest trees of the temperate zone

Abstract: Summary Information on the onset of the leaf senescence in temperate deciduous trees and comparisons on its assessment methods are limited, hampering our understanding of autumn dynamics.We compare five field proxies, five remote sensing proxies and two data analysis approaches to assess leaf senescence onset at one main beech stand, two stands of oak and birch and three ancillary stands of the same species in Belgium during 2017 and 2018.Across species and sites, onset of leaf senescence was not significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 62 publications
1
61
1
Order By: Relevance
“…The first one is the ‘Park of Brasschaat’ (PB), the second one is the military domain ‘Klein Schietveld’ (KS), a Natura2000 reserve. The study areas are at the distance of 9,5 km, in a region with topography flat and without any features possibly causing significant climatological differences ( Mariën et al., 2019 ). Both areas encompass planted (oak and beech) and unplanted stands (birch) on sandy soil, with low management activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one is the ‘Park of Brasschaat’ (PB), the second one is the military domain ‘Klein Schietveld’ (KS), a Natura2000 reserve. The study areas are at the distance of 9,5 km, in a region with topography flat and without any features possibly causing significant climatological differences ( Mariën et al., 2019 ). Both areas encompass planted (oak and beech) and unplanted stands (birch) on sandy soil, with low management activity.…”
Section: Methodsmentioning
confidence: 99%
“…The onset of leaf senescence was defined as the point in time (breakpoint) when the seasonal canopy coloration sharply increased due to the start of the natural process of leaf senescence (before this point slight coloration already happened due to slow build-up of leaf stress damage). Details about the determination of the leaf senescence onset at the study sites can be found in ( Mariën et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The loss of canopy greenness was observed for the same tree individuals and four additional tree individuals per species and site (thus for 32 trees in total). The two forests and their meteorological conditions are described in detail by Mariën et al (2019), which also showed a lack of site effects on the autumn chlorophyll dynamics for the tree species studied here. To have a larger statistical sample, the data of the two beech stands (also of similar age and stem diameter) were aggregated.…”
Section: Methodsmentioning
confidence: 79%
“…In principle, the onset of autumn leaf senescence could be derived from the CCI or loss of canopy greenness. However, Mariën et al (2019) recently showed that the latter method cannot be used under severe drought stress. Therefore, two phenological variables were considered to describe the autumn canopy dynamics: the onset of autumn leaf senescence derived from the CCI (the onset of autumn leaf senescenceCCI) and the onset of the loss of canopy greenness.…”
Section: Using Breakpoints To Indicate the Onset Of Autumn Leaf Senesmentioning
confidence: 99%
See 1 more Smart Citation